Natural or artificial: An example of topographic spatial distribution analysis of mescaline in cactus plants by matrix-assisted laser desorption/ionization mass spectrometry imaging - Lin, Jiaman; Yang, Shuo; Ji, Jiaojiao; Xiang, Ping; Wu, Lina; Chen, Hang (Frontiers in Plant Science, 2023)
Differentiating whether plant products are natural or artificial is of great importance in many practical fields, including forensic science, food safety, cosmetics, and fast-moving consumer goods. Information about the topographic distribution of compounds is an important criterion for answering this question. However, of equal importance is the likelihood that topographic spatial distribution information may provide important and valuable information for molecular mechanism study. In this study, we took mescaline, a substance with hallucinogenic properties in cacti of the species Trichocereus pachanoi and Lophophora williamsii, as an example to characterize the spatial distribution of mescaline in plants and flowers by liquid chromatograph-mass spectrometry–matrix-assisted laser desorption/ionization mass spectrometry imaging at the macroscopic, tissue structure, and even cellular levels. According to our results, the distribution of mescaline in natural plant was concentrated on the active meristems, epidermal tissues, and protruding parts of Trichocereus pachanoi and Lophophora williamsii, while artificially spiked Lophophora diffusa products showed no such difference in their topographic spatial distribution. This difference in distribution pattern allowed us to distinguish between flowers that could synthesize mescaline on their own and those that had been artificially spiked with mescaline. The interesting topographic spatial distribution results, such as the overlap of the mescaline distribution map and micrographs of the vascular bundles, were consistent with the synthesis and transport theory of mescaline, indicating the potential for applying matrix-assisted laser desorption/ionization mass spectrometry imaging in botanical research.